New diketopiperazines as vectors for peptide protection and brain delivery: Synthesis and biological evaluation. (9th September 2016) - Virgone‐Carlotta, A.; Dufour, E.; Bacot, S.; Ahmadi, M.; Cornou, M.; Moni, L.; Garcia, J.; Chierici, S.; Garin, D.; Marti‐Batlle, D.; Perret, P.; Ghersi‐Egea, J.F.; et al.
Abstract : New strategies allowing the transfer of molecules, especially peptides, through the blood‐brain barriers are a major pharmacological challenge for the treatment of brain diseases. The present study aims at evaluating in vivo the cerebral bioavailability of carrier systems, based on small and functionalizable 2, 5‐diketopiperazine (DKP) motifs. We studied 2 different cyclo(Lys‐Lys) DKP scaffolds alone and a cyclo(Lys‐Gly) DKP carrier bearing as peptide model, the tau protein hexapeptide VQIVYK sequence. The different carrier systems were synthesized and radiolabeled using one of the free domains. The stability, biodistribution, and ability to cross blood‐brain barrier were investigated in vivo in mice for 99m Tc‐DKP scaffolds, 99m Tc‐HVQIVYK peptide alone, and 99m Tc‐DKP‐VQIVYK. 125 I‐labelled bovine serum albumin was used as negative control for brain uptake. Both radiolabeled DKPs scaffolds and 99m Tc‐DKP‐VQIVYK showed a high stability, while peptide 99m Tc‐HVQIVYK alone was quickly degraded in vivo. The presence of 99m Tc‐DKPs scaffolds and 99m Tc‐DKP‐VQIVYK was observed in the ventricular and subarachnoid spaces and to a lower extent in the brain parenchyma up to 45 minutes post‐injection in mice. This work highlights the potentiality of DKP scaffolds as vectors to transport peptides into the brain by limiting proteolysis and favoring cerebral bioavailability. Abstract : We evaluated the cerebral bioavailability of 99m Tc‐diketopiperazine (DKP) carriers. The DKPs scaffolds and a DKP derivative bearing the VQIVYK sequence were evaluated. Radiolabeled DKPs scaffolds and DKP‐VQIVYK showed a high stability in vivo . The radiolabeled peptide HVQIVYK alone was quickly degraded after injection in mice. A retention of DKPs scaffolds and DKP‐VQIVYK was observed in vivo into the brain.